Poised transcription factories prime silent uPA gene prior to activation. - Carmelo Ferrai; Sheila Q Xie; Paolo Luraghi; Davide Munari; Francisco Ramirez; Miguel R Branco; Ana Pombo; Massimo P Crippa (PLoS Biology)
The position of genes in the interphase nucleus and their association with functional landmarks correlate with active and/or silent states of expression. Gene activation can induce chromatin looping from chromosome territories (CTs) and is thought to require de novo association with transcription factories. We identify two types of factory: "poised transcription factories," containing RNA polymerase II phosphorylated on Ser5, but not Ser2, residues, which differ from "active factories" associated with phosphorylation on both residues. Using the urokinase-type plasminogen activator (uPA) gene as a model system, we find that this inducible gene is predominantly associated with poised (S5p(+)S2p(-)) factories prior to activation and localized at the CT interior. Shortly after induction, the uPA locus is found associated with active (S5p(+)S2p(+)) factories and loops out from its CT. However, the levels of gene association with poised or active transcription factories, before and after activation, are independent of locus positioning relative to its CT. RNA-FISH analyses show that, after activation, the uPA gene is transcribed with the same frequency at each CT position. Unexpectedly, prior to activation, the uPA loci internal to the CT are seldom transcriptionally active, while the smaller number of uPA loci found outside their CT are transcribed as frequently as after induction. The association of inducible genes with poised transcription factories prior to activation is likely to contribute to the rapid and robust induction of gene expression in response to external stimuli, whereas gene positioning at the CT interior may be important to reinforce silencing mechanisms prior to induction.